2021
DOI: 10.1007/s10921-021-00757-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Flaw Data to Machine Learning Powered Ultrasonic Inspection

Abstract: Previous research (Li et al., Understanding the disharmony between dropout and batch normalization by variance shift. CoRR abs/1801.05134 (2018). http://arxiv.org/abs/1801.05134arXiv:1801.05134) has shown the plausibility of using a modern deep convolutional neural network to detect flaws from phased-array ultrasonic data. This brings the repeatability and effectiveness of automated systems to complex ultrasonic signal evaluation, previously done exclusively by human inspectors. The major breakthrough was to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Even when using only one image for generating training patches, the combined data augmentation achieved a good a 90/95 result. With pure virtual flaw augmentation, used by Koskinen et al [27], there can be a loss of some subtle features related to the combination of location and signal, not perfectly captured by virtual flaw, which is then alleviated by mixing defects in their original locations and new locations. Moreover, the distribution of flaw sizes and shapes is slightly skewed from the original, the effect of which is reduced by having half of the data set follow the original distribution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even when using only one image for generating training patches, the combined data augmentation achieved a good a 90/95 result. With pure virtual flaw augmentation, used by Koskinen et al [27], there can be a loss of some subtle features related to the combination of location and signal, not perfectly captured by virtual flaw, which is then alleviated by mixing defects in their original locations and new locations. Moreover, the distribution of flaw sizes and shapes is slightly skewed from the original, the effect of which is reduced by having half of the data set follow the original distribution.…”
Section: Discussionmentioning
confidence: 99%
“…This is a simpler approach in comparison to simulation methods [13,33] that require each defect type to be modeled in a representative way. Koskinen et al [27] also found simulation to yield limited generalization. In the case of cracks, the combined method did not differ from pure virtual, since no cracks from the original material were present in the training data set, but they were rather used for validation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For more details, we refer to [ 18 , 19 , 20 ] and the references therein. For each gear wheel, the raw signal of acoustic response that goes through a preamplifier was recorded by two receivers (channels 1 and 2) with a sampling rate of 1041.67 kHz with respect to ten different positions:…”
Section: Materials Furthermore Methodsmentioning
confidence: 99%